2011
DOI: 10.1016/j.neuropsychologia.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traumatic brain injury on a virtual reality social problem solving task and relations to cortical thickness in adolescence

Abstract: Social problem solving was assessed in 28 youth ages 12-19 years (15 with moderate to severe traumatic brain injury (TBI), 13 uninjured) using a naturalistic, computerized virtual reality (VR) version of the Interpersonal Negotiations Strategy interview (Yeates, Schultz, & Selman, 1991). In each scenario, processing load condition was varied in terms of number of characters and amount of information. Adolescents viewed animated scenarios depicting social conflict in a virtual microworld environment from an ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 77 publications
1
34
0
Order By: Relevance
“…Other studies reported only a specific severity grouping, such as severe TBI , or mild TBI (Anderson et al, 2001). Not all studies documented cause of injury, but those that did reported that most instances of TBI were due to motor vehicle accidents (passenger and pedestrian), or falls (Anderson et al, 2001;Fletcher et al, 1990;Ganesalingam et al, 2006Ganesalingam et al, ,2007aGanesalingam et al, ,2007bHanten et al, 2011;Max et al, 1998;Papero et al, 1993;Stronach and Turkstra, 2008). With the exception of Hanten and associates (2008), and Newsome and colleagues (2010), the studies did not report on lesion/pathology location with regard to social competence in the TBI groups, and when brain imaging data were included the information was relatively non-specific (e.g., frontal or subcortical).…”
Section: Methodological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies reported only a specific severity grouping, such as severe TBI , or mild TBI (Anderson et al, 2001). Not all studies documented cause of injury, but those that did reported that most instances of TBI were due to motor vehicle accidents (passenger and pedestrian), or falls (Anderson et al, 2001;Fletcher et al, 1990;Ganesalingam et al, 2006Ganesalingam et al, ,2007aGanesalingam et al, ,2007bHanten et al, 2011;Max et al, 1998;Papero et al, 1993;Stronach and Turkstra, 2008). With the exception of Hanten and associates (2008), and Newsome and colleagues (2010), the studies did not report on lesion/pathology location with regard to social competence in the TBI groups, and when brain imaging data were included the information was relatively non-specific (e.g., frontal or subcortical).…”
Section: Methodological Factorsmentioning
confidence: 99%
“…Severe: GCS ÂŁ 8 Moderate: GCS score 9-12 or higher with abnormal neuroimaging Hanten et al (2008) Moderate: GCS score 9-12 or 13-15 with brain lesions indicated by CT; Severe: GCS 3-8 Hanten et al (2011) Severe: GCS score 3-8 Moderate: GCS score 9-12 or GCS score 13-15 with brain lesions indicated by CT scans…”
Section: Social Outcomesmentioning
confidence: 99%
“…[35,36] Despite the broad use of VR-based therapy for balance-focused rehabilitation in neurologically similar populations, the use of VR for the physical rehabilitation of patients with TBI has been limited, [35][36][37]97] with the majority of research focusing on cognitive rehabilitation. [31,[98][99][100][101][102][103][104][105][106] Applications of VR have sparsely been used for physical rehabilitation [37] and functional training, including completing kitchen activities, [32,98] using automatic teller machines, [107] driving [108][109][110] and wayfinding. [111] In regards to balance, VR has been investigated as a tool to assess deficits post injury in athletes with mild TBI, [112][113][114] and as a therapeutic technique to treat long-term balance deficits in patients more than six months post TBI.…”
Section: Emerging Techniques For Balance Treatments: Virtual Realitymentioning
confidence: 99%
“…1 Childhood TBI is also linked to deficits in social information processing (SIP) across domains that include executive function, 2 theory of mind, 3 and social problem-solving. 4 For example, children with TBI exhibit problems making inferences about the mental states of others and show impairments on traditional theory of mind tasks. 3 Theory of mind is closely linked with executive functions such as working memory and inhibitory control, especially early in childhood.…”
Section: Introductionmentioning
confidence: 99%